DESENVOLVIMENTO E CARACTERIZAÇÃO DE NANOPARTÍCULAS LIPÍDICAS CONTENDO HALCINONIDA PARA MODULAÇÃO DA INFLAMAÇÃO NO PROCESSO DE CICATRIZAÇÃO DE LESÕES CUTÂNEAS - Lopes, Clarissa Elize (2015)
Skin wounds are interruptions of the normal physiological and anatomical structure of the skin causing damage by loss of barrier function becoming the organism exposed to various types of substances and microorganisms. A fast healing of the wound is essential to avoid the risk of infections and other complications. The aim of this work was to the development of lipid nanoparticles, as solid lipid nanoparticles and lipid-core polymeric nanoparticles containing halcinonide to modulate the inflammatory phase of wound healing, reducing pain, discomfort, edema, exudates and to reduced the drug toxicity. To this end, nanoparticles were obtained and characterized for particle size, physicochemical properties, stability, encapsulation efficiency, scanning electron microscopy by field emission, x-ray diffraction, spectroscopy in the infrared and Raman Fourier Transform, differential scanning calorimetry, thermal gravimetric analysis, study of the in vitro skin permeation and in vivo evaluation of the inflammatory response and drug toxicity. Furthermore, a highperformance liquid chromatography method for quantification of the drug was developed and validated. Nanoparticles had an average diameter ranging from 260-500 nm, polydispersity index below 0.37, zeta potential close to -30 mV, pH between 5.3 and 6.5 and were stability after storage for 60 days. The microscopy images showed spherical shape with smooth surface. The X-ray diffraction analysis showed drug amorphization in the nanostructured systems. By infrared and Raman spectroscopy was identified the characteristic bands of main components of the formulations, indicating no chemical bonding between them. Thermal analysis revealed the melting peaks of the drug and lipids and polymer and the temperature of its degradation. Nanoparticles showed 5.0% of drug permeation in 24 hours. In vivo study showed that the pure halcinonide was toxic; producing systemic adverse effects and nanoparticles containing the drug was able to modulate the inflammation healing, avoiding the edema and exudates formation and however impairing the subsequent stages of the healing process. However, the incorporation of the halcinonide in nanoparticles was able to reduce the drug toxicity due to the control of the drug release. Regarding the samples of lipid nanoparticles, both showed similar results, wherein the lipid-core polymeric nanoparticles showed better retraction of the wound and macroscopic appearance, possibly due to the polymer control associated with the lipid in halcinonide release.